2014
DOI: 10.1080/15583058.2014.935983
|View full text |Cite
|
Sign up to set email alerts
|

ANTAEUS Project for the Regional Vulnerability Assessment of the Current Building Stock in Historical Centers

Abstract: This paper presents a methodology for the seismic vulnerability assessment of current buildings, suitable for the study of historical centres at the regional scale. The applicability is demonstrated with reference to four case studies: the historical centre of the city of Foggia (Italy) and three other small towns of this province, for a total of 4519 housing units. Field data were collected by several teams of technicians by means of a survey form, provided in electronic format. The subsequent data processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…It is also known that the building classification can be done differently under different construction and seismic settings. For example, masonry buildings in Europe are separated depending on the structural material (stone, brick, concrete block), floor diaphragm type (flexible wood or rigid concrete) and the quality of material and construction [8,9,16,27,28]. Conducted building inventories in Eastern Canada identified two main types of unreinforced masonry (URM): stone masonry [15] and brick masonry [17] which, as the most frequent ones, were retained for this study.…”
Section: Background Of the Methodologymentioning
confidence: 99%
“…It is also known that the building classification can be done differently under different construction and seismic settings. For example, masonry buildings in Europe are separated depending on the structural material (stone, brick, concrete block), floor diaphragm type (flexible wood or rigid concrete) and the quality of material and construction [8,9,16,27,28]. Conducted building inventories in Eastern Canada identified two main types of unreinforced masonry (URM): stone masonry [15] and brick masonry [17] which, as the most frequent ones, were retained for this study.…”
Section: Background Of the Methodologymentioning
confidence: 99%
“…Top concrete slab has a thickness of 4 cm, minimum value which Italian code considers to assume the hypothesis of rigid floor. Strength class of concrete is 25/30, according to [4]. In the reference case, it is considered only dead load, neglecting non-structural and accidental loads.…”
Section: Structural Fem Modelsmentioning
confidence: 99%
“…Existing RC buildings are mostly characterized by an unsatisfactory level of the technical design (mainly because the reference building codes are very obsolete), and the development of vulnerability studies is one of the main research focus that the scientific community has explored in the last years at different scales of analyses [1,2,3,4]. These studies, together with the observation of post-seismic damage after recent earthquakes, have clearly shown that the seismic risk of existing RC buildings is very high, confirming the need of systematically assessing their safety level and to develop to this aim not only proper techniques for the modeling and analysis but also for the monitoring and control, especially in the case of strategic structures [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…High uncertainties characterize the seismic assessment procedures both at building and regional level [1]. Although significant advances were made to improve the procedures for the input selection and in the development of refined analysis methods, difficulties are still present.…”
Section: Introductionmentioning
confidence: 99%